Placebo use in the United kingdom: results from a national survey of primary care practitioners. - Howick, J; Bishop, F; Heneghan, C; Wolstenholme, J; Stevens, S; Hobbs, R; Lewith, G (Public Library of Science, 2013)
OBJECTIVES: Surveys in various countries suggest 17% to 80% of doctors prescribe 'placebos' in routine practice, but prevalence of placebo use in UK primary care is unknown. METHODS: We administered a web-based questionnaire to a representative sample of UK general practitioners. Following surveys conducted in other countries we divided placebos into 'pure' and 'impure'. 'Impure' placebos are interventions with clear efficacy for certain conditions but are prescribed for ailments where their efficacy is unknown, such as antibiotics for suspected viral infections. 'Pure' placebos are interventions such as sugar pills or saline injections without direct pharmacologically active ingredients for the condition being treated. We initiated the survey in April 2012. Two reminders were sent and electronic data collection closed after 4 weeks. RESULTS: We surveyed 1715 general practitioners and 783 (46%) completed our questionnaire. Our respondents were similar to those of all registered UK doctors suggesting our results are generalizable. 12% (95% CI 10 to 15) of respondents used pure placebos while 97% (95% CI 96 to 98) used impure placebos at least once in their career. 1% of respondents used pure placebos, and 77% (95% CI 74 to 79) used impure placebos at least once per week. Most (66% for pure, 84% for impure) respondents stated placebos were ethical in some circumstances. CONCLUSION AND IMPLICATIONS: Placebo use is common in primary care but questions remain about their benefits, harms, costs, and whether they can be delivered ethically. Further research is required to investigate ethically acceptable and cost-effective placebo interventions.